A comparative study of lens management in the United Kingdom and India with regard to rhegmatogenous retinal detachment surgery. Issue 5 (September 2020) - Brent, Alexander J; Bedi, Sahiba; Wakefield, Matthew; Banerjee, Somnath
Introduction: Lens management in phakic patients with rhegmatogenous retinal detachments undergoing para plana vitrectomy surgery remains controversial among vitreoretinal surgeons. When combined phacovitrectomy is performed, the biometry decisions can be challenging both in the face of macula-off rhegmatogenous retinal detachments and previous refractive surgery. This study analyses current trends in practise. Methods: A scenario-related survey was sent to all members of the British and Eire Association of Vitreoretinal Surgeons and to vitreoretinal surgeons in the northern Indian state of Punjab. Results: In post-laser-assisted in situ keratomileusis patients with a visually significant cataract and a macula-on rhegmatogenous retinal detachment, the majority of British and Eire Association of Vitreoretinal Surgeons members (67.3%) and surgeons in Punjab (91.4%) would perform a stand-alone para plana vitrectomy and defer cataract surgery. When a combined phacovitrectomy is performed in this scenario, the majority of British and Eire Association of Vitreoretinal Surgeons (68%) would implant an intraocular lens (using either Haigis-L or European Society of Cataract and Refractive Surgeons/American Society of Cataract and Refractive Surgeons calculators), whereas the majority of Punjab surgeons (79.3%) would leave the patient aphakic. In a patient with a cataract and macula-off rhegmatogenous retinal detachment undergoing combined phacovitrectomy surgery, without any previous refractive surgery, the majority of British and Eire Association of Vitreoretinal Surgeons members (47.3%) would use the opposite eye biometry, whereas most Punjab surgeons (62.7%) would leave the patient aphakic. Discussion: Vitreoretinal surgeons in both the United Kingdom and Punjab predominantly avoid combined surgery in rhegmatogenous retinal detachment cases, even when faced with a visually significant cataract. When combined phacovitrectomy is performed, most vitreoretinal surgeons preference using the opposite eye biometry for macula-off cases and Haigis-L (myope) or online calculators for post-laser-assisted in situ keratomileusis cases.